Philippine Electrical Code 2000 : Part 1, Volume 2 (Quezon City, Philippines : Philippines Institute of Integrated Electrical Engineers of the Philippines, 2002)
The Philippine Electrical Code Part 2 (PEC 2) was adopted for the first time by the Electrical Engineering Board in Board Resolution No. 12 dated December 20, 1973 and approved by the Professional Regulation Commission. THis is denominated as the First Edition of the Philippine Electrical Code Part 2 which was published by the Philippine Society of Electrical Engineers (PSEE) in 1974.
Chapter 10. Watercraft .
Includes index.
Keywords: ELECTRICAL ENGINEERING -- CODE